Management of adolescents with very poorly controlled type 1 diabetes by nurses: a parallel group randomized controlled trial. Issue 1 (December 2015) - Kassai, Behrouz; Rabilloud, Muriel; Bernoux, Delphine; Michal, Catherine; Riche, Benjamin; Ginhoux, Tiphanie; Laudy, Valérie; Terral, Daniel; Didier-Wright, Catherine; Maire, Veronique; Dumont, Catherine; Cottancin, Gilles; et al.
Abstract Backgrounds Fluctuation in glycemia due to hormonal changes, growth periods, physical activity, and emotions make diabetes management difficult during adolescence. Our objective was to show that a close control of patients' self-management of diabetes by nurse-counseling could probably improve metabolic control in adolescents with type 1 diabetes. Methods We designed a multicenter, randomized controlled, parallel group, clinical trial. Seventy seven adolescents aged 12–17 years with A1C >8 % were assigned to either an intervention group (pediatrician visit every 3 months + nurse visit and phone calls) or to the control group (pediatrician visit every 3 months). The primary outcome was the evolution of the rate of A1C during the 12 months of follow-up. Secondary outcomes include patient's acceptance of the disease (evaluated by visual analog scale), the number of hypoglycemic or ketoacidosis episodes requiring hospitalization, and evaluation of A1C rate over time in each group. Results Seventy-seven patients were enrolled by 10 clinical centers. Seventy (89.6 %) completed the study, the evolution of A1C and participants satisfaction over the follow-up period was not significantly influenced by the nurse intervention. Conclusion Nurse-led intervention to improve A1C did not show a significant benefit in adolescents with type 1 diabetes because of lack of power. Only psychological management and continuous glucose monitoring have shown, so far, a slight but significant benefit on A1C. We did not show improvements in A1C control in teenagers by nurse-led intervention. Trial registration Clinical Trials.gov registration number:NCT00308256, 28 March 2006.